Analisis Tingkah Laku LGBT pada Film Spongebob Squarepants di Episode 49b - Riswanto, Riswanto; Hartati, Elni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research examines the existence of LGBT behavior in the Spongebob Squarepants film in episode 49b with the rock-a-bye bivalve theme. This film also presents stories, events, music and other studies on the film Spongebob Squarepants, a cartoon film that is widely watched and loved by children. Written by Stephen Hillenburg and directed by Sean Dempsey. This research is aimed at gaining a deeper understanding of LGBT (Lesbian, Gay, Bisexual, Transgender) behavior towards transgender people. This research is a qualitative descriptive research, where this research will analyze, take notes, take pictures and interpret each meaning of the word dialogue. The method used in this research uses Charles Sanders Peirce's semiotic analysis which uses the theory of three main elements, namely signs, reference signs (Objects) and user signs (Interpretation). there are four scenes from several other scenes. From the results of the research, there were found baby shells, showing off in terms of clothing, doing housewife work and wearing purple dresses while looking after the baby. Through the character Spongebob, this film shows how he acts as a housewife and Patrick as a father who does not participate in helping Spongebob with his work. Apart from that, there is a sign meaning that appears in each selected scene, there is a Transgender sign from the film Spongebob Squarepants which expresses their gender identity through the way they speak, act, dress and style their hair. Keywords: Film, LGBT behavior, Spongebob Squarepants, Charles Semiotics